Discover, Reuse and Share Knowledge on Service Oriented Architectures - Soto Carrión, Jesús; Shu, Lei; Garcia Gordo, Elisa (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Current Semantic Web frameworks provide a complete infrastructure to manage ontologies schemes easing information retrieval with inference support. Ideally, the use of their frameworks should be transparent and decoupled, avoiding direct dependencies either on the application logic or on the ontology language. Besides there are different logic models used by ontology languages (OWL- Description Logic, OpenCyc-FOL, ...) and query languages (RDQL, SPARQL, OWLQL, nRQL, etc..). These facts show integration and interoperability tasks between ontologies and applications are tedious on currently systems. This research provides a general ESB service engine design based on JBI that enables ontology query and reasoning capabilities thought an Enterprise Service Bus. An early prototype that shows how works our research ideas has been developed.
Keywords: Service Oriented Architectures; Distributed Computing; Semantic; IJIMAI